EFFECT OF COMBINED BOBATH AND BALANCE EXERCISE THERAPY ON PHYSICAL MOBILITY IMPROVEMENT IN STROKE PATIENTS: A CASE STUDY - Sri Sulistiyawati; Yurike Septianingrum; Umdatus Soleha; Lono Wijayanti (Literasi Kesehatan Husada)
Background: Stroke emerged as a serious global health problem, ranking as the leading cause of disability and the second leading cause of death worldwide. The most common impact of stroke was impaired physical mobility, especially with damage to the brain's motor centers or nerve pathways controlling body movements. In stroke patients, this disorder could appear directly after an acute attack and persist into the rehabilitation phase if not treated properly. One intervention to address physical mobility disorders in stroke patients was the application of a combination of Bobath therapy and balance exercises to accelerate motor function recovery, prevent immobilization complications, and increase patient independence.